MiR‐148a‐3p regulates proliferation and apoptosis of bovine muscle cells by targeting KLF6. Issue 9 (22nd February 2019) - Song, Chengchuang; Yang, Jiameng; Jiang, Rui; Yang, Zhaoxin; Li, Hui; Huang, Yongzhen; Lan, Xianyong; Lei, Chuzhao; Ma, Yun; Qi, Xinglei; Chen, Hong
Abstract: Skeletal muscle development is regulated by a series of regulatory factors, and also including noncoding RNA, especially microRNAs (miRNAs). Recently, miR‐148a has been found to be involved in murine C2C12 differentiation by targeting ROCK1 . However, the function of miR‐148a‐3p for the proliferation and apoptosis of bovine muscle cells has not been determined. In this study, we found that miR‐148a‐3p was highly expressed in fetal bovine skeletal muscle and exhibited a decreasing trend in muscle cells during its growth phase. Functional studies indicated that gain of miR‐148a‐3p inhibited the proliferation of bovine muscle cells and promoted apoptosis. Conversely, interference with miR‐148a‐3p inhibitor promoted muscle cell proliferation and inhibited its apoptosis. Mechanistically, KLF6 was confirmed as a new potential target gene of miR‐148a‐3p by TargetScan software prediction and the dual‐luciferase assay verification. Additionally, after a gain or loss of KLF6, the function of KLF6 for muscle cell proliferation and apoptosis was opposite to that of miR‐148a‐3p. Collectively, these findings proposed a novel avenue whereby miR‐148a‐3p impeded bovine myoblast cell proliferation and promoted apoptosis through the posttranscriptional downregulation of KLF6 . Abstract : Our research investigates that the function of microRNA (miR)‐148a‐3p in bovine myoblast cells is to inhibit proliferation and promote apoptosis. Our prediction and experimental verification found that KLF6 is a potential target gene of miR‐148a‐3p.